Defectos de diseño del euro: problemas inherentes al Banco Central Europeo - Fernández, Daniel (Papeles de Europa, 2014)
In the midst of Great Recession come up in Europe many doubts about the design of the European currency. The aim of this paper is to establish what kind of issues could have been avoided with a more efficient currency and monetary institutions design. Most of these oversights are due to underestimate redistribution function that could carry on through monetary system or the transfer of risk that could happen from private sector to public sector or between different States inside the European Monetary Union. Finally we treat monetary issues derived from interest rate arbitrages between different terms and the long term credit abuse and the inexistence of a mechanism to limit its expansion.
Keywords: monetary system; liquidity; means of payment; credit